A qualitative investigation of uninsured patient and primary care provider perspectives on specialty care eConsults - Lauren Bifulco; Lynsey Grzejszczak; Idiana Velez; Tracy Angelocci; Daren Anderson (BMC, 2023)
Abstract Background Uninsured and underinsured patients face specialty care access disparities that prevent them from obtaining the care they need and negatively impact their health and well-being. We aimed to understand how making specialty care electronic consultations (eConsults) available at a multi-site Federally Qualified Health Center (FQHC) in central Texas affected uninsured patients' care-seeking experiences and impacted their ability to receive the needed care. Methods We used concepts from Ecological Systems Theory to examine individual, interpersonal, organization-level, social, and health policy environment factors that impacted patients' access to specialty care and the use of eConsults. We conducted thematic analysis of semi-structured, qualitative interviews with patients about seeking specialty care while uninsured and with uninsured patients and FQHC PCPs about their experience using eConsults to obtain specialists' recommendations. Results Patients and PCPs identified out-of-pocket cost, stigma, a paucity of local specialists willing to see uninsured patients, time and difficulty associated with travel and transportation to specialty visits, and health policy limitations as barriers to obtaining specialty care. Benefits of using eConsults for uninsured patients included minimizing/avoiding financial stress, expanding access to care, expanding scope of primary care, and expediting access to specialists. Concerns about the model included patients' limited understanding of eConsults, concern about cost, and worry whether eConsults could appropriately meet their specialty needs. Conclusions Findings suggest that eConsults delivered in a primary care FQHC addressed uninsured patients' specialty care access concerns. They helped to address financial and geographic barriers, provided time and cost savings to patients, expanded FQHC PCPs' knowledge and care provision options, and allowed patients to receive more care in primary care.